SENIOR LEARNERS, ANDRAGOGY, GERAGOGY, AND SYNTHETIC PHONICS: A CASE STUDY - Bhroin, Aine Ni (University of Saint Joseph, 2023)
Although there is a substantial body of research on the second language acquisition of adults, there is little specific research on the learning experiences of senior and very senior adults. This thesis investigates and discovers the experience of being a senior from a traditional Confucian Heritage Culture aged between 55 and 75 years old, learning English as a foreign language through various interventions, including, the introduction of an adapted version of synthetic phonics to improve pronunciation, alongside the use of andragogical and geragogical principles to accommodate and encourage the development of agency and self-directed learning. This research adopted a case study methodology to investigate the lived experiences of seniors, and investigated the participants’ subjective constructions of the situation, learning experiences, challenges, circumstances, needs, and wants with regard to the situation. Therefore, an open and exploratory case study design was selected to understand the participants and report the findings. Furthermore, this thesis identifies the challenges faced by senior and very senior learners who are post-work and post-family rearing to make recommendations from the findings to complement, enhance and empower their learning
Keywords: ANDRAGOGY; GERAGOGY; SENIORS; SYNTHETIC PHONICS; Thesis and Dissertations PhD in Education (D-SE); University of Saint Joseph

A Mixed-methods Study on Teachers' Perceptions of the Use of Drama-in-education In Secondary English Classrooms in Macau - Leong, Si Kei (University of Saint Joseph, 2024)
Drama-in-Education (DiE) has been recognised as a valuable teaching pedagogy in the western world for decades, and yet it has not been fully or systematically adopted in the secondary English classes in Asian contexts, including Macau, despite the numerous reported advantages for English language teaching (ELT) in the past studies. This study explores Macau’s secondary school English teachers’ perceptions of utilising DiE in their classes. A mixed-methods research (MMR) approach was adopted in this study, consisting of three phases. First, pre-survey interviews were conducted to understand the potential major concerns about the choices of teaching approaches and the application of DiE of Macau’s secondary school English teachers. Subsequently, a questionnaire survey targeting local secondary school English teachers was administered, the results of which were cross-examined by, and integrated with, the results of two post-survey group interviews. While the results affirm the local secondary school English teachers’ positive view on DiE as an ELT pedagogy and identify their perceived advantages of DiE, the study indicates the over-determination of multi-faceted challenges to its implementation in Macau’s secondary education context. The study identifies and recommends necessary substantial changes to further the application of DiE in Macau’s secondary education milieu
Keywords: Drama; Drama-in-Education (DiE); English language teaching (ELT); English teachers; Macau; Secondary schools; Thesis and Dissertations PhD in Education (D-SE); University of Saint Joseph

ACQUISITION OF HIGHER-ORDER THINKING SKILLS IN SECONDARY EDUCATION: A CASE STUDY IN A MACAU SECONDARY ESL CONTEXT - Siu, Ka U. (University of Saint Joseph, 2024)
This study examined the acquisition of higher-order thinking skills in an English as a Second Language (ESL) classroom at a secondary school in Macau. It included an investigation of the way teaching might affect the development of higher-order thinking skills and language proficiency. This study also included an examination of the degree to which existing societal practices or values might have influenced the acquisition of higher-order thinking skills. Research instruments such as a questionnaire, a twelve-week experiment, pre-and post-tests and interview sessions were used for the data collection. The findings suggested that after twelve weeks the experimental groups developed higher synthetical and evaluative skills than the control groups which instead demonstrated better language skills. The results also identified incongruences between the curriculum and the expectations of the parents and employers
Keywords: ESL Learning; Thesis and Dissertations PhD in Education (D-SE); University of Saint Joseph; critical thinking; higher-order thinking skills

Parents, students and secondary schools in Macao - Tchiang, Van Man (University of Saint Joseph, 2009)
Macao, a developing city, has been undergoing rapid and significant changes economically, culturally, and socially, partly as a consequence of the changes to the economy brought about by the gaming and tourism industry. Changes in Macao have had a major impact on its schools. Parents have a significant impact on students in school, and Macao’s secondary schools are having to handle a range of challenges and problems brought by students and their parents, many of these as a result of the changes in the wider society of Macao. The response of many schools to the challenges faced is limited, and they understate and under-use the important role played by more developed forms of parental involvement in schools. This study examines the nature, scope and extent of the problems that secondary schools in Macao are having to handle from parents and students, how the schools are handling them, and what needs to be done in order to address the problems and handle them more effectively. Through a large scale survey, interviews and a small scale questionnaire, the thesis identifies key problems facing the schools from students and parents, and it reveals that many of Macao’s secondary schools are ill-equipped to handle these, and there are many signs that the problems are becoming more acute. The thesis finds that negative parental behavior has had a stronger effect on students than positive parental behavior, and it finds that there are several reasons why the schools, in their present state, cannot address these matters effectively. A significant gap is found between what the schools indicate they should be doing and what they are actually doing to address increased parental involvement in order to impact positively on Macao’s students. Recommendations are made for intervention and action
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

COGNITIVE PROCESSES IN ENGLISH SOURCE-BASED WRITING OF MACAO ENGLISH AS A FOREIGN LANGUAGE (EFL) UNIVERSITY STUDENTS - Peralta, Rachel Luna (University of Saint Joseph, 2024)
Source-based summary writing is an important aspect of academic writing at the undergraduate level; it includes summarizing and paraphrasing when producing texts in essay, report, or thesis formats. For university students whose second language or foreign language is English, source-based writing can be a challenging task as it involves and requires complex cognitive processes as well as reading-and-writing demands. Organized into three phases, this mixed method, small-scale exploratory feasibility case study investigated: (i) challenges and difficulties in online and offline English source-based summary writing of English as a Foreign Language (EFL) university students in Macao, identifying the cognitive and writing processes they experienced in a timed reading-writing task; and (ii) how to design and conduct interventions that could be used to diagnose, assess, and address essay challenges in source-based summary essay writing in everyday classroom sessions. Quantitative and qualitative data were collected through a summary online writing essay using Inputlog, a keystroke logging software, and retrospective think-aloud protocol in Phase One, a source-based summary essay writing task in a quasi-experiment in Phase Two, and a survey questionnaire and error analysis of pre-test and post-test essays of the control and experimental groups in Phase Three. The processes of reading and writing in English were found to be challenging and complex for EFL university students to perform in a limited time. As an initial exploratory feasibility, efficacy trial, deliberately small scale to address issues of risk, this study found that the diagnostic assessment tools and interventions had the potential to improve the summary writing processes and proficiency of EFL students, focusing on their cognitive writing skills in everyday class sessions. The thesis recommends scaling up the research in future studies, in terms of sampling and the duration of interventions designed to improve source-based summary essay writing and the cognitive writing processes that are part of this
Keywords: EFL university students; Thesis and Dissertations PhD in Education (D-SE); University of Saint Joseph; cognitive processes; source-based writing

PERCEPTIONS OF, AND ATTITUDES TO CATHOLIC SCHOOLS’ IDENTITY AND ETHOS IN MACAO: TOWARDS A COMMON FRAMEWORK OF CATHOLIC SCHOOLS’ IDENTITY - The Reh, Lawrence (University of Saint Joseph, 2024)
The thesis identifies concerns preserving, maintaining, and developing the Catholic identity of Catholic schools in Macao, the largest providers of schooling whilst being a minority religion, and with its teachers, parents, and students coming from Catholic and non-Catholic backgrounds, cultures, and values. To understand the present situation of Catholic identity in Macao’s Catholic schools, manifesting itself in part through the Catholic ethos of schools, and to identify key features, mission, vision, values, and areas for the development of Catholic identity, together with its presence and practices, this thesis reports a study of the perceptions of, and attitudes to, Catholic identity held by three key stakeholder parties in a carefully chosen representative selection of Catholic schools: teachers, parents, and students. The thesis reports their views on what the Catholic schools are currently doing in the areas of Catholic identity, and what they consider that they should be doing in these areas. The areas of focus draw on scholarship and teachings on Catholic identity, with particular emphasis placed on documents on Catholic identity and ethos from the Vatican, Archbishop Miller, and Monsignor Stock. A large-scale empirical survey here found that there was considerable support for Catholic schools in Macao, their identity, ethos, and values from the three parties. Two emergent patterns of findings are reported concerning the steps that Catholic schools were taking to promote their identity: (a) what Catholic schools should be doing concerning Catholic identity received consistently higher scores than what they were currently doing; and (b) consistently higher support for Catholic identity came from the teachers, slightly less so from the parents, and slightly less than that from the students. The study conducted a follow-up, small-scale study to investigate why these might be the case, and it suggested that the combination of Catholic values and Chinese cultural features might explain the findings on Catholic identity in the schools. The study identifies areas for possible development of, and improvements to, the identity of Catholic schools, that take account of the local cultural contexts and the teachings of the Catholic church on identity, and how these might be addressed in practice
Keywords: Catholic Schools' Ethos; Catholic Schools' Identidy; Catholic schools; Thesis and Dissertations PhD in Education (D-SE); University of Saint Joseph

English as a foreign language: a comprehensive study on teacher's self-efficacy and its antecedents in Macao - Lam, Man Ieng; Malungu, Laurie Baker; Negreiros, João Garrott Marques (University of Saint Joseph, 2019)
As societies globalize, mastery of a second or multiple languages has become an important index to enhance interaction in the society. In that English is a is a widely used medium of communication globally for engagement in international business, commerce, science, technology and governance, the benefits of an efficacious English language teaching force to facilitate the English acquisition process of students in classrooms around the world is highly valued. For the purpose of this study, the English language teacher efficacy instrument (ELTEI) was adapted to the local context to measure the professional efficacy of the English as a foreign language (EFL) teacher participants. The objective of the research was to investigate the degree of relationship between antecedent conditions and specific teacher efficacy in Macao. A mixed-method approach in a sequential phase design was adopted to explore the efficacy of English language teachers serving Chinese medium schools in a non-English speaking region in Asia. Phase-one employed a qualitative approach to contextualize the measurement instrument and to ascertain important characteristics of the target population. Phase-two ensured a quantitative approach to yield understanding regarding the influence of key antecedent conditions on the efficacy of English language teachers in Macao. As evidenced through multiple linear regressions and structural equation modeling, openness, neuroticism, and perceived school support were significant predictors for teacher’s self-efficacy in English teaching. Recommendations for the school management to enhance and sustain the efficacy of EFL teachers in Macao were discussed
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

INTEGRATING VARIATION THEORY WITH MULTILINGUAL INSTRUCTION IN MULTILINGUAL CLASSROOMS: BRIDGING THEORY AND PRACTICE IN FOREIGN LANGUAGE ACQUISITION - Gomes, Nuno Miguel Alves dos Santos Teixeira; Correia, Ana Maria; Thota, Neena Jawaharlal (University of Saint Joseph, 2023)
This thesis explores language teaching and language acquisition by multilingual learners using a Variation Theory approach and multilingual teaching in a university setting in Macao, China. It includes three case studies applied to students of the Spanish language in the introductory level which took place from late August to early December of the year 2017. The first study describes Macao’s multilingual language learners in the University of Macao in 2017. Based on the LEAP-Q questionnaire, a questionnaire was created to inquire all Spanish language students about their languages´ background, their motivations to learn new languages, as well as their learning strategies. The second study shows how the usage of Variation Theory techniques and multilingual teaching techniques boosted the teaching and the learning during the semester. This study employs a case study methodology, by analysing in-class multiple interactions gathering information on how multilinguals´ language background affects the pedagogical process. It analyses a total of 28 classes of 1 hour and 15 minutes. The third study presents the analysis of a questionnaire to 82 students of the initial level of Spanish language in the University of Macao, along with the analysis of interviews from 10 selected multilingual students about their linguistic background and how they experienced the semester. These interviews collected more information about the effectiveness of the Variation Theory in the semester in terms of in-class teaching and learning. From the triangulation of these three studies, some conclusions have been drawn about the advantages of using Variation Theory and multilingual teaching techniques for multilingual students, for the language teacher and ultimately also into the curricular design of foreign language teaching. In sum, that the linguistic background of students plays a major role in how they acquire a new language and, that applying Variation Theory techniques can be an immensely effective technique in a language classroom setting; suggesting that multilingual students will gain from being previously identified and placed in a separate class where these variation techniques were applied. Since this thesis focuses solely on an introductory language course, there is ground to explore this same approach on more advanced multilingual language learners
Keywords: Foreign language teaching; Multilingualism; Thesis and Dissertations PhD in Education (D-SE); University of Saint Joseph; Variation Theory